2020
DOI: 10.1186/s13229-020-00382-x
|View full text |Cite
|
Sign up to set email alerts
|

Functional relationships between recessive inherited genes and genes with de novo variants in autism spectrum disorder

Abstract: Background Both de novo variants and recessive inherited variants were associated with autism spectrum disorder (ASD). This study aimed to use exome data to prioritize recessive inherited genes (RIGs) with biallelically inherited variants in autosomes or X-linked inherited variants in males and investigate the functional relationships between RIGs and genes with de novo variants (DNGs). Methods We used a bioinformatics pipeline to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…The gnomAD pRec score, which represents the probability of intolerance to biallelic loss of function, was higher in these genes than other genes (Mann-Whitney test: p=0.0004). Five of these genes ( SYNE1, FAT1, VPS13B, DNAH3, and ITGB4 ) have previously been associated with ASD (Krumm et al, 2015; Wang et al, 2020). ITGB4 was also identified in the TADA+ analysis, suggesting that it may confer ASD susceptibility in a dose-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…The gnomAD pRec score, which represents the probability of intolerance to biallelic loss of function, was higher in these genes than other genes (Mann-Whitney test: p=0.0004). Five of these genes ( SYNE1, FAT1, VPS13B, DNAH3, and ITGB4 ) have previously been associated with ASD (Krumm et al, 2015; Wang et al, 2020). ITGB4 was also identified in the TADA+ analysis, suggesting that it may confer ASD susceptibility in a dose-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…Despite ASD being highly heritable, inherited defects in single genes are rare ( Schaefer et al, 2013 ) and most identified single gene mutations are de novo ( O'Roak et al, 2014 ; Wang et al, 2020 ). Even when both chromosomal microarray and whole exome sequencing are used, the unbiased empirical clinical genetic evaluations demonstrate low yields (−16%) ( Tammimies et al, 2015 ) and only 31% of the time do siblings with ASD have the same de novo single gene mutations ( Yuen et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the high apparent heritability, empirical studies suggest that structural genetic defects account for a minority of ASD cases with empirical studies finding that a genetic disorder can be found in only about 16% of children with ASD using both a chromosomal microarray and whole exome sequencing [20]. In addition, when a variant is found, it is usually de novo rather than inherited [21][22][23][24]. In fact, there is insufficient evidence for a ASD-specific gene or a particular genetic variant with a large effect [25].…”
Section: Structural Dna Alterationsmentioning
confidence: 99%